Biogenic amines: formation, action and toxicity – a review - Wójcik, Wojciech; Łukasiewicz, Monika; Puppel, Kamila (Journal of the science of food and agriculture, 2021)
Biogenic amines (BA) are organic compounds commonly found in food, plants and animals, as well as microorganisms that are attributed with the production of BAs. They are formed as an effect of a chemical process: the decarboxylation of amino acids. Factors determining the formation of BAs include the availability of free amino acids and the presence of microorganisms that show activity with respect to carrying out the decarboxylation process. On the one hand, BAs are compounds that are crucial for maintaining cell viability, as well as the proper course of the organism's metabolic processes, such as protein synthesis, hormone synthesis and DNA replication. On the other hand, despite their positive effects on the functioning of the organism, an excessive content of BAs proves to be toxic (diarrhea, food poisoning, vomiting, sweating or tachycardia). Moreover, they can accelerate carcinogenesis. Amines are a natural component of plant and animal raw materials. As a result of the proven negative effects of amines on living organisms, the reduction of these compounds should be the subject of scientific research. The present review aims to synthesize and summarize the information currently available on BAs, as well as discuss the interpretation of the results. © 2020 Society of Chemical Industry